Bullying Case Analysis: Types, Contributing Factors, Impacts, and Prevention in Junior High School - Wiwin Haryani; Supriyoko Supriyoko; Rahayu Retnaningsih (AL-ISHLAH: Jurnal Pendidikan, 2025)
Bullying in schools remains a critical issue despite the implementation of various prevention programs. The persistent increase in cases suggests that current interventions lack a holistic approach. This study investigates the forms, impacts, and prevention strategies of bullying in a junior high school context. A qualitative descriptive study was conducted using a single-case study design at SMPN 3 Pedan. Data were collected through semi-structured interviews and direct observations involving students (victims, perpetrators, witnesses), teachers, and school staff selected via purposive sampling. The Miles and Huberman model guided data analysis, involving data reduction, presentation, and conclusion drawing. Four primary types of bullying were identified: verbal, social, mild physical, and cyberbullying, with verbal bullying being the most prevalent. The psychological impacts included anxiety, low self-esteem, and social withdrawal, while physical effects such as sleep disturbances and somatic complaints were also reported. Cyberbullying showed more severe and lasting consequences. Existing school responses were found to be inadequate due to the absence of a clear reporting mechanism, vague disciplinary measures, and limited stakeholder involvement. Findings highlight the urgent need for a comprehensive, restorative approach to address bullying. This includes teacher and staff training, implementation of a confidential reporting system, and integration of character education and digital literacy into the school culture to build a safer and more inclusive environment.